Planejamento protético para pacientes adultos portadores de fissura labiopalatal congênita, que não obtiveram oportunidade de um tratamento reabilitador ideal: execução de casos clínicos para pacientes selecionados - Figueiredo, Aldari Raimundo [UNESP] (1992)
Although one cannot prevent the birth of human beings with cleft palate lesions one can adopt attitudes and various procedures entirely viable to rehabilitate and recuperate these persons through a team work composed of the facilities of a hospital, physician, dentist, psychotherapist, epeech pathologist, pedagogue and a social worker. In order to reduce the suffering of these patients we took up this work to prove that even if not in an ideal manner nevertheleses in an acceptable one we can reintegrate these persons to their families, friends and social milieu, offering them more security in their social, psychic and human relationships. We have made a review of the literature during the last three decades where we found many possibilities of prosthetic recuperations which concerns esthetics, mastication and maxillomandibular relationships beyond allowing these pacients conditions to perform satisfactory the functions of deglution and speech. We have selected and executed 5 clinical cases out of 15 pacients formely choosen looking to different prosthetic plannings. We have also shown the major contribution that the osseous integrated implants can offer to the rehabilitation and recuperation of pacients whith congenitall labio palatal lesions. To simplify the understanding we tried to discuss the most varied types of prosthesis in well defined subjects having a separate approach for each of them and we still showed that the specificity of each case leads to a specific type of rehabilitation founded om esthetics, occlusion, osseous suport, edentulous space, and above all based in the common sense and Professional integrity